Gabon : Request for a Three-Year Extended Arrangement under the Extended Fund Facility-Press Release; Staff Report; Supplementary Information, and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2021)
The Gabonese economy was gradually recovering from the 2014 oil price shock when it was hit by the Covid-19 pandemic. Decisive confinement measures have helped save lives, but the pandemic and the fall in oil prices have severely hit the economy, increasing unemployment and poverty. With a weak economy and increased COVID-19 related spending, the fiscal deficit has widened, with a sharp increase in public debt. Emergency financing from the IMF through the Rapid Financing Instrument (USD 299.61 million) helped meet urgent balance of payment needs in 2020. Growth is expected to resume in 2021 but the pandemic has made the economic outlook very challenging and generated sizable financing needs over the medium term.